2014
DOI: 10.1146/annurev-pathol-020712-163936
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Innate and Adaptive Immune Responses on Atherosclerosis

Abstract: Both the chronic development of atherosclerotic lesions and the acute changes in lesion phenotype that lead to clinical cardiovascular events are significantly influenced by the innate and adaptive immune responses to lipoprotein deposition and oxidation in the arterial wall. The rapid pace of discovery of mechanisms of immunologic recognition, effector functions, and regulation has significantly influenced the study of atherosclerosis, and our new knowledge is beginning to affect how we treat this ubiquitous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
196
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 243 publications
(201 citation statements)
references
References 175 publications
(213 reference statements)
1
196
1
3
Order By: Relevance
“…It has been suggested that a Th2-biased response per se might be atheroprotective independent of the immunogen ( 46 ). To study this, we generated a similar, Th2-biased response to a lipid peroxidation-derived adduct, but one that we did not expect to be abundant in vivo, nor relevant to atherogenesis.…”
Section: Fifth: Nonspecifi C Igg1-th2-biased Immune Responses Per Se mentioning
confidence: 99%
“…It has been suggested that a Th2-biased response per se might be atheroprotective independent of the immunogen ( 46 ). To study this, we generated a similar, Th2-biased response to a lipid peroxidation-derived adduct, but one that we did not expect to be abundant in vivo, nor relevant to atherogenesis.…”
Section: Fifth: Nonspecifi C Igg1-th2-biased Immune Responses Per Se mentioning
confidence: 99%
“…This in turn leads to further endothelial damage and may induce epigenetic changes that can cause phenotypic alterations. [22][23][24][25] Since exogenous nucleic acids can stimulate the PRRs and trigger endothelial activation and inflammation, nucleic acid therapies must be cloaked by nanoparticle delivery systems as described below.…”
Section: Role Of Nucleic Acid Construct In Regulating Endothelial Funmentioning
confidence: 99%
“…22 Several research groups have reported that oxidative injury-induced DAMPs primarily drive the innate-immune response associated with a dysfunctional endothelium. 25 Recent studies have reported altered mitochondrial dynamics and endoplasmic reticulum-induced stress as factors initiating EC activation. 27,28 Alterations in the function of these organelles may modulate endothelial nitric oxide synthase (eNOS) activity, alter barrier function, and prompt endothelial cell migration and angiogenesis.…”
Section: Damps Pamps and Endothelial Dysfunctionmentioning
confidence: 99%
“…The ubiquity of these epitopes led Witztum to propose that OSEs form a family of DAMPs that initiate a sterile inflammation aimed at removing dangerous biological waste produced during oxidative processes [7,8]. It is now apparent that OSEs are among the most important inducers of inflammatory responses not only in atherosclerosis, but also in other inflammatory diseases, and that they are potential targets for diagnosis and therapy [7,9,10]. The danger model proposed by Polly Matzinger states that the immune system is more concerned with detection of damage than with foreignness and is called into action by alarm signals from injured tissues rather than by those that are simply foreign [11].…”
Section: Vision Article Open Accessmentioning
confidence: 99%